The Holy Spirit and the Son's Glorification: Spirit Christology as a Theological Lens for Interpreting John 7:37-39 - Sánchez M., Leopoldo A. (Journal of theological interpretation, 2018)
In John 7:37-39, Jesus promises "rivers of living water" to those who believe in him. John explains that such reference is to "the Spirit," which "had not been given, because Jesus was not yet glorified" (RSV). The text has puzzled interpreters through the centuries. First, who does the "rivers of living water" (v. 38) flow fromJesus or the believer? Second, was not the Spirit around before the Son's glorification, which for John begins with his being lifted up on the cross? If so, then in what sense is the Spirit yet to be given (v. 39)? We will argue that a Spirit Christology, which speaks of Jesus as the receiver, bearer, and giver of God's Spirit, is a most promising theological framework to make sense of Jesus' words in John 7, unlock the pneumatic dynamic and trajectory of the Gospel as a whole, and more broadly, to ask important theological questions of the text in dialogue with interpreters past and present.